Lumican is increased in experimental and clinical heart failure, and its production by cardiac fibroblasts is induced by mechanical and proinflammatory stimuli. (2nd April 2013) - Engebretsen, Kristin V. T.; Lunde, Ida G.; Strand, Mari E.; Waehre, Anne; Sjaastad, Ivar; Marstein, Henriette S.; Skrbic, Biljana; Dahl, Christen P.; Askevold, Erik T.; Christensen, Geir; Bjørnstad, Johannes L.; Tønnessen, Theis
Abstract : During progression to heart failure (HF), myocardial extracellular matrix (ECM) alterations and tissue inflammation are central. Lumican is an ECM‐localized proteoglycan associated with inflammatory conditions and known to bind collagens. We hypothesized that lumican plays a role in the dynamic alterations in cardiac ECM during development of HF. Thus, we examined left ventricular cardiac lumican in a mouse model of pressure overload and in HF patients, and investigated expression, regulation and effects of increased lumican in cardiac fibroblasts. After 4 weeks of aortic banding, mice were divided into groups of hypertrophy (AB) and HF (ABHF) based on lung weight and left atrial diameter. Sham‐operated mice were used as controls. Accordingly, cardiac lumican mRNA and protein levels were increased in mice with ABHF. Similarly, cardiac biopsies from patients with end‐stage HF revealed increased lumican mRNA and protein levels compared with control hearts. In vitro, mechanical stretch and the proinflammatory cytokine interleukin‐1β increased lumican mRNA as well as secreted lumican protein from cardiac fibroblasts. Stimulation with recombinant glycosylated lumican increased collagen type I alpha 2, lysyl oxidase and transforming growth factor‐β1 mRNA, which was attenuated by costimulation with an inhibitor of the proinflammatory transcription factor NFκB. Furthermore, lumican increased the levels of the dimeric form of collagen type I, decreased the activity of the collagen‐degrading enzyme matrix metalloproteinase‐9 and increased the phosphorylation of fibrosis‐inducing SMAD3. In conclusion, cardiac lumican is increased in experimental and clinical HF. Inflammation and mechanical stimuli induce lumican production by cardiac fibroblasts and increased lumican altered molecules important for cardiac remodeling and fibrosis in cardiac fibroblasts, indicating a role in HF development. Abstract : Lumican was increased in the failing heart of mice and men. In vitro cyclic mechanical stretch and inflammation induced lumican expression and protein secretion from cardiac fibroblasts. Moreover, increased lumican in cardiac fibroblasts induced expression of molecules important for cardiac remodeling and fibrosis, suggesting a role for lumican in heart failure development.